'So debatable a subject, and viewed with so much suspicion': Theology in the University: Australia. Issue 3 (2nd October 2021) - Burns, Stephen
ABSTRACT: Although marked by suspicion reaching back to sectarianism among early colonisers, theology endures in Australian institutions – albeit not always being welcome in universities. Creative responses to exclusion from university contexts have emerged over time – some more stable, others quite fragile. However, colonialism morphs across the sector, and longstanding injustices remain unresolved. This article charts institutional developments and then explores gender and colonial history as areas of ongoing tension.